The Morning Star in Semba Scarves as a Source of Ideas For Creating Batik Motifs for Casual Wear - Firdaus, Roihatal Jannati; Sudarwanto, Aan (Institut Seni Indonesia Surakarta, 2023)
This Final Project entitled